1994
DOI: 10.1128/jb.176.18.5665-5672.1994
|View full text |Cite
|
Sign up to set email alerts
|

The leucine-responsive regulatory protein binds to the fim switch to control phase variation of type 1 fimbrial expression in Escherichia coli K-12

Abstract: Phase variation of type 1 fimbriation in Escherichia coli is associated with the site-specific recombination of a 314-bp DNA invertible element. Thefim switch directs transcription offimA, the major fimbrial subunit gene, in one orientation (on) but not the other (off). Switching requires eitherfimB (on-to-off or off-to-on inversion) or fimE (on-to-off inversion only) and is reduced sharply in strains containing lrp::TnlO mutations. Both fimE-promoted switching andfimB-promoted switching are stimulated by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
103
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(104 citation statements)
references
References 23 publications
0
103
1
Order By: Relevance
“…Likewise, a shift to a lower antibiotic concentration for the ⌬hns and ⌬lrp backgrounds harboring pBAD-tosR-His 6 does not perturb TosR regulation itself; the lower antibiotic concentration did not perturb TosR-mediated regulation in the wild-type E. coli CFT073 background (data not shown). As for H-NS, Lrp is also a global regulator (19,22,(37)(38)(39)(59)(60)(61)(62)(63)(64)(65)(66)(67). Therefore, it remains unclear if additional gene products also supplement Lrp-and TosRmediated positive regulation of the tos operon.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, a shift to a lower antibiotic concentration for the ⌬hns and ⌬lrp backgrounds harboring pBAD-tosR-His 6 does not perturb TosR regulation itself; the lower antibiotic concentration did not perturb TosR-mediated regulation in the wild-type E. coli CFT073 background (data not shown). As for H-NS, Lrp is also a global regulator (19,22,(37)(38)(39)(59)(60)(61)(62)(63)(64)(65)(66)(67). Therefore, it remains unclear if additional gene products also supplement Lrp-and TosRmediated positive regulation of the tos operon.…”
Section: Resultsmentioning
confidence: 99%
“…Some genes regulated by Lrp are positively or negatively regulated by exogenous leucine (63)(64)(65)67). To test whether exogenous leucine positively or negatively regulates the tos operon, we performed our pBAD-lrp overexpression assay in the CFT073 ⌬tosR background in M9 minimal medium with and without exogenous leucine (10 mM).…”
Section: Resultsmentioning
confidence: 99%
“…The orientation was confirmed by restriction analysis. The minimal fim switch unit was cloned into pDG19, using primers 135F and 136F, generating pNJH79 for allelic exchange into strain BGEC144, generating strain ZAP973, as described in Gally et al (1994). Insertion was confirmed by specific PCR.…”
Section: Methodsmentioning
confidence: 99%
“…Lrp, for instance, slightly affects the transcription of both fimB and fimE. Additionally, it also binds with high affinity within the fim switch, and this binding stimulates recombination in both directions (Gally et al, 1994). In the case of H-NS, it has been shown that H-NS is a repressor of the FimB recombinase, but there is evidence that this regulation is not the sole cause of the increased DNA flipping observed in hns mutant backgrounds (Donato et al, 1997).…”
Section: Control Of Fimbrial Expressionmentioning
confidence: 99%
“…FimE, on the other hand, causes only switching from phase-ON to phase-OFF (Blomfield et al, 1991;Gally et al, 1996). In addition to the fim recombinases, efficient inversion of the fim switch requires the accessory proteins integration host factor (IHF) and leucine-responsive regulatory protein (Lrp) (Blomfield et al, 1993(Blomfield et al, , 1997Dorman & Higgins, 1987;Gally et al, 1994). The histone-like nucleoid-structuring protein (H-NS) is also involved in the recombination event (Donato et al, 1997;O'Gara and Dorman, 2000;Olsen & Klemm, 1994).…”
Section: Introductionmentioning
confidence: 99%